Sustainable Turkey Farming: The Role of Hydroponic Sprouted Fodder in Feed Optimization - Yasmin, Kanis; Rashedi, Mobasser Ahmed; Mehta, Basant Kumar; Salma, Ummay; Miah, Abdul Gaffar (International Journal of Applied Sciences and Biotechnology, 2025)
Hydroponic fodder has gained attention as an innovative and sustainable feed resource for poultry production. This study assessed the effects of hydroponic maize and sesbania sprouted fodder as partial replacements for commercial concentrate feed (CCF) in turkey production, with a focus on growth parameters, feed intake, feed conversion efficiency (FCE), and economic viability. Forty-eight turkeys (eight-week-old) were randomly divided into four dietary treatment groups: T1 (100% CCF), T2 (90% CCF + 10% hydroponic fodder), T3 (70% CCF + 30% hydroponic fodder), and T4 (60% CCF + 40% hydroponic fodder). Results revealed that hydroponic maize contained 14.79% dry matter (DM) and 10.92% crude protein (CP), while sesbania had 9.46% DM and 37.26% CP, demonstrating its potential as a high-protein alternative. Among the treatment groups, the highest (P